PERCEIVED ORGANIZATIONAL SUPPORT, KARAKTERISTIK TIM, QUALITY OF WORK LIFE DAN KOMITMEN ORGANISASI: STUDI PADA PEGAWAI UNIVERSITAS NEGERI JAKARTA - Heru Santosa (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2016)
The objective of this research was to obtain information concerning the effect of perceived organizational support, team characteristics and quality of work life toward employee organizational commitment at the State University of Jakarta by using a survey method with path analysis applied in testing hypothesis. It involved 64 employee at the State University of Jakarta as respondent who were selected by simple random sampling. This research findings were as follows (1) there was a direct effect of perceived organizational support toward organizational commitment; (2) there was a direct effect of team characteristics toward organizational commitment; (3) there was a direct effect of quality of work life toward organizational commitment; (4) there was a direct effect of perceived organizational support toward quality of work life; (5) there was a direct effect of team characteristics toward quality of work life. Therefore, organizational commitment could be improving by rising the effect of perceived organizational support, team characteristics and quality of work life.